The Policy Of Preventing And Handling Of Sexual Violence In Universities In Kalimantan - Erlina, Erlina; Erniyati, Tiya; Athaya, Deva Fadhil; Khairiani, Ulfa; Al Fisah Jannah, Ristia (Scholar Center, 2022)
This research is a study in the field of Social Humanities and Gender Studies related to the Regulation of the Minister of Education, Culture, Research, and Technology Number 31 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education, to see how it is implemented at State Universities in Kalimantan. The purpose of this study is to identify and describe the perceptions of leaders of state universities in Kalimantan on the meaning of the Ministerial Regulation on the Prevention and Handling of Sexual Violence in Higher Education and the patterns used in its implementation; besides that, it is also to analyze the achievements and obstacles in the implementation of prevention and handling of sexual violence in universities in Kalimantan. This study uses a socio-legal research method with an interdisciplinary approach between normative research aspects through the study of legislation related to the theme of the study and a sociological approach to explore problems, perceptions and follow-up actions taken by the leadership of the leading State Universities in Kalimantan, such as Lambung Mangkurat University, Tanjung Pura University, Mulawarman University, Palangkaraya University and Borneo Tarakan University after the issuance of the Ministerial Regulation related to the prevention and handling of Sexual Violence in Higher Education.